Rare ovarian tumours: Epidemiology, treatment challenges in and outside a network setting. Issue 1 (January 2019) - ,; Hackl, Monika; Van Eycken, Elizabeth; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Purpose of the review: More than 50% of all gynaecological cancers can be classified as rare tumours (defined as an annual incidence of <6 per 100, 000) and such tumours represent an important challenge for clinicians. Recent findings: Rare cancers account for more than one fifth of all new cancer diagnoses, more than any of the single common cancers alone. Reviewing the RARECAREnet database, some of the tumours occur infrequently, whilst others because of their natural history have a high prevalence, and therefore appear to be more common, although their incidence is also rare. Harmonization of medical practice, guidelines and novel trials are needed to identify rare tumours and facilitate the development of new treatments. Ovarian tumours are the focus of this review, but we comment on other rare gynaecological tumours, as the diagnosis and treatment challenges faced are similar. Future: This requires European collaboration, international partnerships, harmonization of treatment and collaboration to overcome the regulatory barriers to conduct international trials. Whilst randomized trials can be done in many tumour types, there are some for which conducting even single arm studies may be challenging. For these tumours alternative study designs, robust collection of data through national registries and audits could lead to improvements in the treatment of rare tumours. In addition, concentring the care of patients with rare tumours into a limited number of centres will help to build expertise, facilitate trials and improve outcomes.